Start and turn performances of elite male swimmers: benchmarks and underlying mechanisms - Born, D.-P.; Kuger, J.; Polach, M.; Romann, M. (Sports Biomechanics, 2021)
The aim was to provide benchmarks and investigate contribution of start and turn performances in the European Short-Course Swimming Championship. Over all race distances, 932 individual races of male competitors were video captured and the start and turn performances were analysed. Start and turn performances contributed up to 26% and 56% of the total race time. Analysis of variance showed that the 15 m start times were faster for Freestyle and Butterfly (p < 0.001) compared to the other swimming strokes. In-water starts (Backstroke) were slower at the 5 m mark compare to on-block starts (p < 0.001). Tumble turns were faster than open turns (p < 0.001). Multiple linear regression analysis explained 82-97% of total variance in the race results with a decreasing effect of start performance for the longer distance races. Turn performance affected the results across all race distances (p < 0.001). The benchmarks and percentiles provide comparative data for swimmers of different performance levels. Considering the large contribution of start and turn performance to race time and the high effect in the regression model, training regimes that are mainly based on conditioning of free-swimming should be reconsidered.